Crystal structures, thermodynamics and accelerating thermal decomposition of RDX: two new energetic coordination polymers based on a Y-shaped ligand of tris(5-aminotetrazole)triazine. (27th August 2019) - Wu, Shuo; Lin, Guowei; Yang, Zhengyi; Yang, Qi; Wei, Qing; Xie, Gang; Chen, Sanping; Gao, Shengli; Lu, Jack Y.
Abstract : Two new energetic coordination polymers were prepared under hydrothermal condition. They have good detonation velocity, detonation pressure and effective acceleration effect toward the thermal decomposition of RDX (1, 3, 5-trinitro-1, 3, 5-triazinane). Abstract : Based on a flexible Y-shaped energetic ligand, tris(5-aminotetrazole)triazine (H3 TATT), two new energetic coordination polymers (ECPs), [Zn2 (HTATT)2 (H2 O)2 ]·3H2 O n (1 ) and [PbZn(TATT)(OH)(H2 O)] n (2 ), have been synthesized under hydrothermal conditions. X-ray single crystal structure analysis shows that both1 and2 are 1D chain structures. Different from1, a large number of hydrogen bond interactions in2 expand it into a 3D supramolecular configuration. The theoretical density and thermal stability of2 are higher than1 . The experimental values of molar heat capacities of1 and2 in the temperature range of 293.15 K–368.15 K are measured by using a DSC instrument and fitted to a polynomial equation of heat capacities by the least squares method. Smoothed heat capacities and thermodynamic functions of1 and2 relative to the standard reference temperature 298.15 K were derived from the fitted polynomial equation. In addition, the theoretical estimation results show that1 and2 possess good detonation velocity and detonation pressure. Sensitivity tests indicate that1 and2 are insensitive to impact and friction stimuli. Furthermore, 1 and2 were explored as combustion promoters to accelerate the thermal decomposition of RDX (1, 3, 5-trinitro-1, 3, 5-triazinane) by differential scanning calorimetry.